STUDI FENOMENOLOGI TENTANG MAKNA BERMAIN PADA PERSPEKTIF PRIA PENGGUNA APLIKASI GAMES HAGO “CHAT SUARA” DALAM MENEMUKAN PASANGAN LAWAN JENIS (JODOH) - Ira Hasianna Rambe, Lusi Romaddyniah Sujana (Jurnal Ilmu Komunikasi, 2019)
Technological developments and knowledge facilitate human beings in all respects. One of them is in interacting without having to meet directly. Unconsciously demanding humans understand what is being hit around it and understand what is again the current trend. One of the applications that many people love today is the online games application. New innovation Games apps, unlike in general that only play individual on the app, but rather this app can play with other real individuals, in this application can also play while chatting, so the competition to win More fun. However, this application is widely used as a matchmaking search event or boyfriend call it Hago application. The application that has 5 features one that is widely loved by men and women is "voice chat". The study uses phenomenological theory as well as qualitative methods with a phenomenological study conducted on twenty informant men of the application games Hago "Voice chat". From the results of this study can be concluded that the meaning of playing games by man users of Hago games "voice chat" as a means of entertainment, establishing relationships, filling the time of the bridegroom, indicating self-existence and maintaining identity Get an appreciation from her environment and find a match. Men using Hago applications are based upon the influence of the surrounding environment as well as on the basis of consciousness.